Neuropathic (Charcot) Arthropathy of the Knee. Issue 23 (1st December 2021) - Rees, Harold; Lyons, Madeline; Belich, Paul; Brown, Nicholas
Abstract : Neuropathic arthropathy of the knee (Charcot knee) is a rare pathology defined by progressive destruction of bone and soft tissue in a patient with underlying peripheral neuropathy. Historically, Charcot knee was associated with neurosyphilis, but it has been increasingly described as a late stage of diabetes. The pathophysiology of the disease is not completely understood, but theories include repetitive microtrauma and an abnormal neurovascular response. Patients present with a warm, swollen, and unstable joint and have rapid bone resorption and characteristic findings on pathology. Nonsurgical options for pain and dysfunction include total contact casting and bracing treatment. Pharmacologic management includes diphosphonates, although this use is considered off-label. Surgical management historically included knee fusion. However, recent case series have suggested that newer prostheses allow for successful arthroplasty in this cohort, although complications are higher when compared with joint arthroplasty in patients with normal neurologic function.